METODE MONITORING DAN EVALUASI : DISKUSI - Nabiu, Musryadi; Sukiyono, Ketut (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
This paper was aimed at discussing a quantitative method for monitoring and evaluation (monev) indevelopment projects. The first part, a current concept and method of monev will be reviewed followed by discussion on monev process focussing on the application of monev on project and sectoral level